2020
DOI: 10.1155/2020/5072938
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ultrasound-Assisted Extraction of Polyphenol Content from Zea mays Hairs (Waste)

Abstract: The aim of this study was to achieve the best extraction efficiency of the hydroethanolic extract of Zea mays hairs. The impacts of ethanol concentration, extraction time, and solvent /material ratio were studied in relation to the performance of Zea mays extracts by ultrasonic extraction at 50 kHz and room temperature. All extracts were quantitatively characterized in terms of polyphenol content. Response surface methodology (RSM) was carried out to optimize the extraction process and increase extraction effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(14 reference statements)
1
5
0
2
Order By: Relevance
“…Similar trends were observed in DPPH and FRAP values, where a liquid-to-solid ratio of 25:1 at the extraction temperature of 40 °C resulted in the highest antioxidant capacity (192 ± 0.09 and 318 ± 0.71 µM Trolox eq/g, respectively) of GSS extract. This was consistent with the mass transfer principle, which indicates that the concentration gradient between solid and liquid is the driving force during mass transfer and rises with increasing solvent-to-sample ratio [ 22 ]. Li et al [ 3 ] found a favourable correlation between procyanidin concentration and liquid-to-solid ratio, which rose rapidly from 5:1 to 15:1 mL/g.…”
Section: Resultssupporting
confidence: 80%
“…Similar trends were observed in DPPH and FRAP values, where a liquid-to-solid ratio of 25:1 at the extraction temperature of 40 °C resulted in the highest antioxidant capacity (192 ± 0.09 and 318 ± 0.71 µM Trolox eq/g, respectively) of GSS extract. This was consistent with the mass transfer principle, which indicates that the concentration gradient between solid and liquid is the driving force during mass transfer and rises with increasing solvent-to-sample ratio [ 22 ]. Li et al [ 3 ] found a favourable correlation between procyanidin concentration and liquid-to-solid ratio, which rose rapidly from 5:1 to 15:1 mL/g.…”
Section: Resultssupporting
confidence: 80%
“…It depends especially on the type of solvent and the matrix used. Table 1 shows that for the extraction of phenolic compounds, the most used solvent is ethanol and the solid-to-solvent ratio varies between 0.025 g/mL [23] and 0.1 g/mL [24], whereas ratios vary between from 0.058 g/mL for the extraction of betacyanin and betaxanthin in bougainvillea flowers [17] to 0.14 g/mL for the extraction of a natural pigment from annatto seeds [16].…”
Section: Variables Influencing Ultrasound-assisted Extractionmentioning
confidence: 99%
“…As mentioned above, the efficiency of the hydroethanolic solution also depends on the food matrix. For example, authors Bamba et al ( 66 ) found a higher efficiency of 50% ethanol (v/v) in the extraction of TFC from blueberry pomace, while authors Aourabi et al ( 67 ) indicated a higher yield of TFC from corn waste when 70% ethanol (v/v) was used. Another phenomenon caused by the process of sonolysis during UAE is increase in the degree of hydroxylation of polyphenolic compounds induced by the formation of OH- radicals as a direct result of sonolysis process on the water molecules in the matrix, thus generally affecting the improvement of the functionality and bioavailability of polyphenols ( 68 , 69 ).…”
Section: Resultsmentioning
confidence: 99%